2021
DOI: 10.1101/2021.04.12.439476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CCR4 blockade leads to clinical activity and prolongs survival in a canine model of advanced prostate cancer

Abstract: Targeting regulatory T cell (Treg) infiltration is an emerging strategy for cancer immunotherapy. However, the efficacy of this strategy in advanced prostate cancer remains unclear. Here, we describe the therapeutic efficacy of this strategy in a canine model of advanced prostate cancer. We used dogs with naturally occurring prostate cancer to study the molecular mechanism underlying Treg infiltration into tumor tissues and the effect of anti-Treg treatment. We found that tumor-infiltrating Tregs were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Importantly, a canine clinical trial revealed that anti-CCR4 treatment with Mogamulizumab improved the survival rate while exhibiting a low rate of clinically relevant adverse effects, providing rationale for the translation of CCR4 blockade therapy to human patients with bladder cancer [189]. The same author reported that the CCR4 blockade led to clinical activity and prolonged survival in a canine model of advanced prostate cancer [190]. Altogether, these works confirmed the feasibility and clinical efficacy of these therapies in the veterinary setting and validated the potential of the canine model for the translation of chemokine-related immune therapies.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Importantly, a canine clinical trial revealed that anti-CCR4 treatment with Mogamulizumab improved the survival rate while exhibiting a low rate of clinically relevant adverse effects, providing rationale for the translation of CCR4 blockade therapy to human patients with bladder cancer [189]. The same author reported that the CCR4 blockade led to clinical activity and prolonged survival in a canine model of advanced prostate cancer [190]. Altogether, these works confirmed the feasibility and clinical efficacy of these therapies in the veterinary setting and validated the potential of the canine model for the translation of chemokine-related immune therapies.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%